Biomonitoring palm oil mill effluent final discharge polluted rivers using molecular-based approaches - Zolkefli, Nurhasliza (2020)
Palm oil industry has been associated with water quality issues from the practice of palm oil mill effluent (POME) final discharge disposal into nearby river. Nevertheless, it is hardly proven since the river is exposed to many other anthropogenic pollutants. The current method for the pollution assessment using physicochemical profiling is less specific. This necessitates the establishment of a complementary molecular-based biomonitoring system where the bacterial indicator and genetic biomarker detections specific for POME pollutants can be utilized. Present study was done to determine the dominant presence of Alcaligenaceae and Chromatiaceae in the POME final discharge polluted rivers in comparison to the other rivers polluted by mining drainage, automotive oil and chemical-related industrial effluents. Based on the capability of Alcaligenaceae to biodegrade lignin derived phenolic compounds, this research was also done to identify the functional genes involved in POME pollutants biodegradation. To achieve the objectives, physicochemical characterization was done to correlate with the detection of the potential bioindicators. 16S rRNA next generation amplicon sequencing was done by Illumina MiSeq, while the bacterial cells viability and nucleic acid activities in all studied rivers were evaluated by utilizing double nucleic acid-based assay of the flow cytometry. In addition, the significant functional genes carried by the bacterial communities involved in the POME biodegradation were screened in the final discharge and polluted rivers by conventional polymerase chain reaction (PCR). Overall, it was confirmed that Alcaligenaceae (0.53% - 0.96%) and Chromatiaceae (0.81% - 3.44%) are dominant in the POME final discharge polluted rivers and not in other polluted rivers. The principle coordinate (PCO) analysis had proved the strong positive correlation between these two bacterial families with 5-day biological oxygen demand (BOD5). Plus, the environmental changes lead to a higher bacterial viability (58.3% - 69.5%) and high nucleic acid (HNA) composition (75.0% - 82.2%) in the POME final discharge polluted rivers as compared to the other polluted rivers with cell viability ranging from 4.4% - 57.6% and HNA from 2.2% - 13.4%. The functional gene screening had resulted with the characterization of phenol hydroxylase and protocatechuate 3,4-dioxygenase genes which are consequentially involved in the degradation of lignin derived phenolic compounds via the β-ketoadipate metabolic pathway. It is impressive that the high intensity of the protocatechuate 3,4-dioxygenase gene at 800 bp was shared only by the bacterial communities in POME final discharges and the receiving downstream rivers but not in the other comparative rivers. These findings prove on the specificity of Alcaligenaceae and Chromatiaceae as the POME final discharge pollution bioindicators in the river and the potential of protocatechuate 3,4-dioxygenase to be used as a molecular biomarker for the detection of this pollutant in the river.